The case for cash - James J. McAndrews (Latin American Journal of Central Banking, 2020)
Cash is an extremely useful social contrivance. Kenneth Rogoff, who calls for phasing-out high denomination cash over time, recently discussed two possible drawbacks of high-denomination cash: the extensive use of high-denomination cash in crime and in illicit and corrupt activities and the role cash plays in preventing deeply negative nominal interest rates imposed on bank accounts. I will argue that using cash is preferable to the alternative, which entails worse types of crimes committed in the absence of cash. Consequently, the current high-denomination cash in the U.S. should be retained.